Risk Factors for Early Weight Loss in Breastfed and Term Newborns - Tijen Eren; Bahar Kural; Emine Gülbin Gökçay (Çocuk Dergisi)
Objective: Newborns lose some of their birth weight before hospital discharge. This loss is accepted as “physiological” up to 5-7%. Infants with weight loss over this range may receive undue formula supplementation. Formula supplementation disrupts exclusive breastfeeding, does not have the benefits of mother’s milk, and may cause low breastfeeding success in the long run. Identification of the risk factors affecting infant weight loss percentage in the few days following the birth will increase exclusive breastfeeding success. The aim of this study is to identify the risk factors that cause early weight loss in newborns before hospital discharge. Material and Methods: Weight loss in infants born between January 1, 2011, and December 31, 2014, at Vehbi Koç Foundation American Hospital was evaluated retrospectively. The hospital records of 3812 babies who completed the inclusion criteria were included in the study. The variables yielding significant results in binary tables were further evaluated by “Multivariate Logistic Regression”. Results: Delivering via caesarean section, primiparity, early term gestational week, older maternal age and female gender of the infant were statistically significant risk factors for early weight loss in newborns. Conclusion: To increase the success of breastfeeding in babies who are exclusively breastfed, the mother-infant pair identified with risk factors that contribute to infant weight loss must be closely monitored. Breastfeeding counselling should be repeated, and breastfeeding should be supported. Suggested intervention list is created aligned with the findings to assist mothers in risk management.